Pemberdayaan Kemandirian Pangan Berbasis Urban Farming di Kawasan Padat Penduduk Kota Surakarta Jawa Tengah - Umi Barokah; Wiwit Rahayu; Darsono Darsono; Sri Marwanti; Minar Ferichani; Ernoiz Antriyandarti; Susi Wuri Ani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
One of the problems faced in providing food from production to urban households is limited land. This also happened in the city of Surakarta. PKK RT 03 RW XVI, Gendingan Jebres village, Jebres Subdistrict, Surakarta City is a group of women who live in densely populated settlements. The problem faced by households in fulfilling family food is dependence on purchases due to limited land for food production. One solution to overcome this problem is to develop urban agricultural activities to support food self-sufficiency. It's just that PKK members do not have knowledge of urban farming, how to apply it, and the infrastructure is limited. Therefore, this community service activity is carried out to solve this problem by conducting counseling and training on urban farming, providing assistance with production facilities in the form of seeds, seedlings, polybags, wall bags, pots, and planting media. In addition, there was also assistance in implementing urban farming for women members of the PKK. Community service activities that have been carried out have made women members of the PKK RT 03 RW XVI, Gendingan Jebres Village, Jebres subdistrict, Surakarta City have knowledge and skills related to urban farming, have urban farming infrastructure so they can implement urban farming in their environment.